Cuvântul – valoare și transfigurare - Șanta, Gheorghe (Yearbook (“Babes-Bolyai” University Cluj-Napoca. Faculty of Orthodox Theology), 2023)
The means by which the Church transmits divine grace to its members are the word of God and the Holy Sacraments. The sacred gift of the word gives man a unique dignity and responsibility, revealing him and imposing him before the world as a speaking and understanding creature. The word through its positive or negative use is and remains one of the most powerful means of transforming or influencing human souls. Through the word of God, spiritual therapy is accomplished. The word of God is addressed to man in order to obtain his salvation, through an absolute synergy, which commits the human person to a permanent endeavor to conform his life to the will of God.